Distinct roles of CSF family cytokines in macrophage infiltration and activation in glioma progression and injury response. Issue 3 (7th June 2013) - Sielska, Malgorzata; Przanowski, Piotr; Wylot, Bartosz; Gabrusiewicz, Konrad; Maleszewska, Marta; Kijewska, Magdalena; Zawadzka, Malgorzata; Kucharska, Joanna; Vinnakota, Katyayni; Kettenmann, Helmut; Kotulska, Katarzyna; Grajkowska, Wieslawa; et al.
Abstract: Gliomas attract brain‐resident (microglia) and peripheral macrophages and reprogram these cells into immunosuppressive, pro‐invasive cells. M‐CSF (macrophage colony‐stimulating factor, encoded by the CSF1 gene) has been implicated in the control of recruitment and polarization of macrophages in several cancers. We found that murine GL261 glioma cells overexpress GM‐CSF (granulocyte–macrophage colony‐stimulating factor encoded by the CSF2 gene) but not M‐CSF when compared to normal astrocytes. Knockdown of GM‐CSF in GL261 glioma cells strongly reduced microglia‐dependent invasion in organotypical brain slices and growth of intracranial gliomas and extended animal survival. The number of infiltrating microglia/macrophages (Iba1 + cells) and intratumoural angiogenesis were reduced in murine gliomas depleted of GM‐CSF. M1/M2 gene profiling in sorted microglia/macrophages suggests impairment of their pro‐invasive activation in GM‐CSF‐depleted gliomas. Deficiency of M‐CSF (op/op mice) did not affect glioma growth in vivo and the accumulation of Iba1 + cells, but impaired accumulation of Iba1 + cells in response to demyelination. These results suggest that distinct cytokines of the CSF family contribute to macrophage infiltration of tumours and in response to injury. The expression of CSF2 (but not CSF1 ) was highly up‐regulated in glioblastoma patients and we found an inverse correlation between CSF2 expression and patient survival. Therefore we propose that GM‐CSF triggers and drives the alternative activation of tumour‐infiltrating microglia/macrophages in which these cells support tumour growth and angiogenesis and shape the immune microenvironment of gliomas. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.